1993
DOI: 10.1080/00224545.1993.9712142
|View full text |Cite
|
Sign up to set email alerts
|

Empathy and Aggression: Effects of Self-Disclosure and Fearful Appeal

Abstract: On the basis of the familiarity-empathy assumption that self-disclosure evokes empathy for the speaker, it was predicted that a victim's self-disclosure would inhibit aggression against the victim. Female Japanese subjects were asked to give electric shocks to a female victim who disclosed information about herself, was not given an opportunity to do so, or rejected disclosure. Independently of self-disclosure, another empathy arousal was introduced, that is, whether or not the victim expressed her fear of sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Prior research has found that revealing personal information about oneself garners greater empathy and facilitates feelings of closeness (Harvey & Omarzu, 1997;Pistrang, Solomons, & Barker, 1999). Personalizing a victim has even been found to decrease aggression towards her: Ohbuchi, Ohno, and Mukai (1993), using a modified teacher-learner paradigm, found that aggression towards the learner-victim was reduced when she revealed personal information about herself prior to receiving "shocks" from the teacheraggressor. Although the source of the personal information in their experiment came from the victim herself rather than from newspaper accounts, the results suggest that personalizing the victim in any way may serve to facilitate empathy.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has found that revealing personal information about oneself garners greater empathy and facilitates feelings of closeness (Harvey & Omarzu, 1997;Pistrang, Solomons, & Barker, 1999). Personalizing a victim has even been found to decrease aggression towards her: Ohbuchi, Ohno, and Mukai (1993), using a modified teacher-learner paradigm, found that aggression towards the learner-victim was reduced when she revealed personal information about herself prior to receiving "shocks" from the teacheraggressor. Although the source of the personal information in their experiment came from the victim herself rather than from newspaper accounts, the results suggest that personalizing the victim in any way may serve to facilitate empathy.…”
Section: Discussionmentioning
confidence: 99%
“…Some work also links overly high self-evaluations to externalizing problems, particularly when these evaluations are challenged (Baumeister, Smart, and Boden 1999;Beck 1999). Research on boundaries finds that extreme connectedness such as emotional reliance raises internalizing symptoms, and extreme individuation such as low empathy increases externalizing problems (Hagan, Gillis, and Simpson 1985;Ohbuchi, Ohno, and Mukai 1992;Guisinger and Blatt 1994;. Other work demonstrates that both autonomy and connection are problematic if unbalanced by the other (Helgeson 1994;Rosenfield et al 2000).…”
Section: Self-salience and Mental Healthmentioning
confidence: 99%
“…Men are less likely to be empathetic and emotionally dependent on intimate partners (Hirschfeld, Klerman, Chodoff, Korchin, & Barrett, 1976; Turner & Turner, 1999). Many theorists suggest that this can be protective against depression, but it can also foster problems with aggression and other externalizing problems (Hagan, Gillis, & Simpson, 1985; Heimer & Coster, 1999; Miedzian, 2002; Ohbuchi, Ohno, & Mukai, 1993; Rosenfield et al, 2000; Turner & Turner, 1999). Men are less likely to express troubles, and are less likely to discuss sensitive issues and solve emotional problems.…”
Section: Introductionmentioning
confidence: 99%